Age and gender influence the cardiorespiratory function and metabolic rate of broiler chicks during normocapnia and hypercapnia - Espinha, Livia P. [UNESP]; Souza, Fernando A. [UNESP]; Capalbo, Aretuza C. [UNESP]; Bicego, Kenia C. [UNESP]; Macari, Marcos [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier B.V., 2014)
Pulmonary ventilation (V-E), body temperature (Tb), mean arterial pressure (MAP), heart rate (f(H)) and metabolic rate (V-O2) were measured in 10 (d10)- and 21 (d21)-day-old male and female chicks exposed to 7% CO2. Under normocapnia, V-E was higher in d10 chicks than in d21 due to a higher tidal volume; in females a higher respiratory frequency (f(R)) was also observed. The d10 birds presented higher f(H) and V-O2. The d21 females showed the highest CO2 ventilatory response due to increased f(R). MAP did not change during hypercapnia while a hypercapnic bradycardia occurred, except in d21 females. Hypercapnia induced a drop in Tb in all groups and an increase in V-O2 in d21 males. Overall, no gender effect is observed in cardiorespiratoly and metabolic variables in d10 and d21 chicks under normocapnia, the differences in V-E and f(H) between ages may be related to distinct metabolic demands of these phases. The d21 female chicks seem to be more sensitive to hypercapnia. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bird; CO2 chemosensitivity; Ventilation; Thermoregulation; Metabolic rate